Kalighat drawing - Archer, W. G (Bombay, 1962)
During the eighteenth century, painting in Bengal consisted of three quite different types. The first is miniature painting executed for the Nawabs of Bengal at their court at Murshidabad.
Keywords: Drawing; ICS as an author; Indian Civil Service